Development of Problem-Based Learning Animation Learning Media to Improve Thematic Learning Outcomes of Grade V Students of SDN 19 Way Serdang, Mesuji Regency - Dwi Yulianti; Rapani Rapani; Lala Dyah Chandra Lala Dyah Chandra; Fitriadi Fitriadi (Yayasan Darussalam Bengkulu, 2026)
This research aims to develop Problem Based Learning (PBL)-based animation learning media and test its feasibility and effectiveness in improving the thematic learning outcomes of grade V elementary school students. The research was carried out at SDN 19 Way Serdang, Mesuji Regency, Lampung, with the research subject of grade V students. The method used is Research and Development (R&D) with reference to the Borg & Gall model as the main development framework that is implemented until the limited trial stage. In the product development process, the ADDIE model is used which includes the analysis, design, development, implementation, and evaluation stages. The research subjects consisted of two classes, namely the VA class as the control group and the VB class as the experimental group. Data was collected through pretest and posttest tests to measure students' thematic learning outcomes, as well as questionnaires to determine students' responses to learning media. The results of the study showed that the PBL-based animation learning media developed met the criteria were very valid based on expert assessment. The increase in student learning outcomes in the experimental class was shown by the increase in the average score from 60 in the pretest to 80 in the posttest. An N-Gain analysis of 0.60 shows an increase in the medium category. In addition, the effect size value of 1.02 shows that the use of media has a great influence on improving students' thematic learning outcomes. Thus, the PBL-based animation learning media developed is declared feasible and effective enough to be used in thematic learning of grade V elementary school students. These findings suggest that the integration of animation media with PBL models can be an innovative alternative in improving the quality of learning and student learning outcomes.